Penyuluhan Bagaimana Menulis Sejarah Desa bagi Perangkat Desa di Desa Walewangko dan Raranon Minahasa - Kembuan, Roger; Kaunang, Ivan Robert Bernadus; Dharyanto Tito Wardani (Universitas Klabat, 2025)
The history of a village plays a crucial role in preserving the heritage and identity of a region. Village history documentation not only serves as a record of valuable events but also strengthens the emotional bond within the community and inspires younger generations. Furthermore, village history can serve as a reference for village heads and local government officials in identifying both the potential and challenges faced by the village, enabling them to make more precise and wise decisions. The main issue found in Walewangko and Raranon Villages, Langowan Barat District, is the absence of comprehensive written historical records. Although the community has the desire to document their village history, limitations in historical writing methods and techniques hinder its realization. Previous efforts have been limited to simple chronological records, which do not provide a complete depiction of the village's history. This community service program is carried out through a historical writing training method. The training team equips participants with materials on historical research methods, techniques for finding historical sources, compiling chronicles, as well as structuring and effectively writing historical narratives. Through this initiative, the community is expected to produce more comprehensive historical documentation, either in the form of historical glimpses or a complete village history. The results of this program are also expected to be published in print and online media, offering broader benefits to the village community and future generations.